Pertanggungjawaban Pihak Maskapai Terhadap Kehilangan dan Kerusakan Bagasi Menurut Peraturan Menteri No. 77 Tahun 2011 Tentang Tanggung Jawab Pengangkut Angkutan Udara - Azis, Fadilah Abd; Abdain, Abdain; Takdir, Takdir (Fakultas Syariah INSURI Ponorogo, 2023)
This research is motivated by the relatively high level of aircraft and passenger security, but it is not comparable to the security of baggage services. The purpose of this research is to describe the form of airline responsibility at Makassar Sultan Hasanuddin International Airport in resolving disputes over loss and damage to passenger baggage, the factors that hinder airline baggage protection, as well as the views of Islamic law in resolving problems regarding forms of airline protection for goods. is lost. passenger baggage. Based on the type of data in this study the authors used an empirical approach with qualitative research data types. The types of materials in this study are primary data and secondary data. Data analysis techniques use three stages of data reduction, data display, and conclusion drawing/verification. The results of the study show that the form of air transport legal responsibility for the loss of damaged passengers is recorded in air transport operated by airlines, namely the airline must provide compensation of IDR 200 thousand per kilogram. , a maximum of IDR 4 million. The inhibiting factors for this protection are the acceptance factor of officers in the field, the engine factor, the negligence factor of the officers, and even the negligence factor of air passengers. In Islamic law, responsibility is known as Mas'uliyyah or Accountability, and the concept of responsibility in Islam is Ta'widh. Ta'widh in language is compensation or compensation.